Wprowadzenie do problematyki records management - Wójtowicz, Radosław (Introduction to electronic records management, 2006)
The article contains the introduction to selected problems concerning records management. The first part presents basic definitions connected with documents and records management. The following part presents the premises for development of records management processes. The last part of the article contains a description of selected legal instruments used in building electronic records management systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 71-78